2012
DOI: 10.1093/mp/sss024
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis LFR Gene Is Required for the Formation of Anther Cell Layers and Normal Expression of Key Regulatory Genes

Abstract: The anther is the male reproductive organ in flowering plants. Although some genes were reported to be involved in anther development, the molecular mechanisms underlying the transcriptional regulation of these genes is unclear. lfr-2 (leaf and flower related-2), the null allele of Arabidopsis thaliana LFR (LEAF AND FLOWER RELATED), was male-sterile. The anthers of lfr-2 plants were defective in sporogenous cell formation, tapetum development, and pollen development. In agreement with these phenotypes, express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
(36 reference statements)
0
18
0
1
Order By: Relevance
“…LFR is very broadly expressed in the different Arabidopsis organs but reaches its highest expression levels in young growing tissue. Mutation of LFR results in a delay in leaf appearance, narrow leaves, and even male sterility (Wang et al, 2009;Wang et al, 2012). LUH is a transcriptional corepressor belonging to the same class as LEUNIG (LUG) (Causier et al, 2012), which was also identified in all performed maize TAP experiments.…”
Section: The Core An3-associated Chromatin Remodeling Complex Is Strumentioning
confidence: 95%
“…LFR is very broadly expressed in the different Arabidopsis organs but reaches its highest expression levels in young growing tissue. Mutation of LFR results in a delay in leaf appearance, narrow leaves, and even male sterility (Wang et al, 2009;Wang et al, 2012). LUH is a transcriptional corepressor belonging to the same class as LEUNIG (LUG) (Causier et al, 2012), which was also identified in all performed maize TAP experiments.…”
Section: The Core An3-associated Chromatin Remodeling Complex Is Strumentioning
confidence: 95%
“…One particular family of interest which was returned in our search results is already characterized in angiosperms: LFR or leaf and flower related [40] . This protein family is required for the development of reproductive structures in flowers and serves as a master regulator of the expression of many reproduction related genes, but its role in lower eukaryotes remains undescribed despite its broad evolutionary conservation.…”
Section: Query With Hap2mentioning
confidence: 99%
“…Most of anther regulatory genes, including TDF1, AMS, AtMYB80 are found to be downstream of DYT1 (Sorensen et al 2003;Zhu et al 2008;Phan et al 2012), and very few seem to occupy the upstream position. As mentioned before, SPL/NZZ and LFR are upstream of DYT1 (Bencivenga et al 2012;Wang et al 2012); however, none of these genes is anther specific and cannot confer DYT1 0 s anther-specific expression. Thus, other unknown upstream gene(s) should collaborate with SPL/NZZ and LFR to confer the male organ-specific expression profile of DYT1.…”
Section: Discussionmentioning
confidence: 80%
“…In Arabidopsis thaliana SPL/NZZ, LFR, EMS1/EXS and TPD1, etc., have been found as DYT1-upstream genes (Yang et al 1999(Yang et al , 2003(Yang et al , 2005Canales et al 2002;Zhao et al 2002;Wijeratne et al 2007;Liu et al 2009;Wang et al 2012). Under the mutant backgrounds of these genes, DYT1 expression is largely down-regulated (Zhang et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation